2021
DOI: 10.1016/j.acap.2021.05.024
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Adverse Childhood Experiences and Weight-Related Health Behaviors in a National Sample of Children

Abstract: The relationship between adverse childhood experiences and weight-related health behaviors in a national sample of children, Academic Pediatrics (2021), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…This study builds upon pre-pandemic research that has demonstrated significant relationships between ACEs and greater digital media use 10 , 11 and lower physical activity 11 by showing that ACEs associated with adolescent sedentary behaviors during the early pandemic. The increase by 2.3 hours increase in screen time is less notable than the three-fold higher difference observed by Jackson et al This more marginal increase may be partially explained by the global increase in screen time and decrease in physical activity of nearly all youth during the early weeks of the pandemic when nearly all schools were closed.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This study builds upon pre-pandemic research that has demonstrated significant relationships between ACEs and greater digital media use 10 , 11 and lower physical activity 11 by showing that ACEs associated with adolescent sedentary behaviors during the early pandemic. The increase by 2.3 hours increase in screen time is less notable than the three-fold higher difference observed by Jackson et al This more marginal increase may be partially explained by the global increase in screen time and decrease in physical activity of nearly all youth during the early weeks of the pandemic when nearly all schools were closed.…”
Section: Discussionmentioning
confidence: 91%
“… 10 A study by Harada, et al, found that ACE exposure in children is associated with lower healthy weight behaviors including elevated screen time and lower rates of physical activity. 11 However, neither of these studies explored the relationship between ACEs and the dramatic changes in adolescent lifestyle behaviors during the pandemic, a time of significant increased family stressors (financial insecurity, social isolation, and health risks). Further, neither of these studies focused on early adolescence, a critical period of development and growth.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a large population-based, cross-sectional survey in US children aged six to seventeen showed negative associations between ACEs and five healthy weight behaviors. The odds of involving in a healthy behavior decreased in a dose-response manner when exposed to more ACEs [ 44 ]. These results supports that children exposed to ACEs with disturbed stress responses impacting the hypothalamic–pituitary–adrenal (HPA) axis [ 45 ] grow up with decreased opportunities to adopt a healthy lifestyle [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The odds of involving in a healthy behavior decreased in a dose-response manner when exposed to more ACEs [ 44 ]. These results supports that children exposed to ACEs with disturbed stress responses impacting the hypothalamic–pituitary–adrenal (HPA) axis [ 45 ] grow up with decreased opportunities to adopt a healthy lifestyle [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 These disparities are often related to contextual differences and social determinants of health, including poverty and socioeconomic status, parental education, early adverse childhood events, and access to healthier food options and safe and affordable physical activity opportunities. [6][7][8][9] Childhood obesity is a multifactorial condition that requires multifaceted systemic approaches to address (1) the root causes of unhealthy weight and related chronic conditions, (2) barriers to access to healthy nutrition, active living, and effective treatment, and (3) disparate prevention and treatment efforts. Major advances in effective treatment of pediatric obesity have occurred over the past decade.…”
mentioning
confidence: 99%